2009
DOI: 10.1073/pnas.0904066106
|View full text |Cite
|
Sign up to set email alerts
|

Neural codes for perceptual discrimination of acoustic flutter in the primate auditory cortex

Abstract: We recorded from single neurons of the primary auditory cortex (A1), while trained monkeys reported a decision based on the comparison of 2 acoustic flutter stimuli. Crucially, to form the decision, monkeys had to compare the second stimulus rate to the memory trace of the first stimulus rate. We found that the responses of A1 neurons encode stimulus rates both through their periodicity and through their firing rates during the stimulation periods, but not during the working memory and decision components of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
106
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(125 citation statements)
references
References 42 publications
12
106
6
Order By: Relevance
“…These results contrast with those obtained in primary auditory cortex (A1) during the same task (9). In that study, we found that A1 neurons responded exclusively during the stimulation periods, but not during the delay periods of the task.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…These results contrast with those obtained in primary auditory cortex (A1) during the same task (9). In that study, we found that A1 neurons responded exclusively during the stimulation periods, but not during the delay periods of the task.…”
Section: Discussioncontrasting
confidence: 55%
“…1A) until their psychophysical thresholds were stable (9). We avoided the issue of task difficulty during the recordings by using a stimulus set that had large differences between f1 and f2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations